Aussie KIDS SAVE LIVES: A position statement from the Australian Resuscitation Council and supported by stakeholders. (13th August 2021) - Bray, Janet; Acworth, Jason; Page, Greg; Parr, Michael; Morley, Peter; ,
Abstract: Every year 25 000 Australians experience a cardiac arrest in our community, but only 12% survive. The faster cardiopulmonary resuscitation and defibrillation, known as basic life support (BLS), is commenced, the greater the chance of survival. Currently, only half of the Australian adults are trained in BLS. The Australian Resuscitation Council and key stakeholder organisations believe that the best way to ensure all Australians know how to save a life is by mandating BLS education and training in our schools. This 'Aussie KIDS SAVE LIVES' position statement outlines our strategy to help facilitate the introduction of a programme of regular BLS training into the Australian school curriculum.